Canna lineata Ciciarelli (Cannaceae-Zingiberales), una especie nueva de los humedales de Buenos Aires, Argentina - Ciciarelli, María de las Mercedes (2014)
Canna lineata is proposed as a species new to science. Plants grow wild both as terrestrial or palustrine, forming dense colonies whose individuals produce large, bright red to reddish orange flowers with narrow staminodes. The specific epithet refers to the colored lines on the vegetative leaves, and floral parts of the androecium. Is related to other species having reduced inflorescences, especially C. glauca, a species widely distributed in tropical and subtropical America. A detailed description of the new species is given, together with a study of morphological vegetative and floral characters especially the labellum and its relation with entomophily.